Случай аномалии зубов у лошади - Рудик, С.К. (Вестник зоологии, 1973)
Anomaly in a number of teeth is described in a horse female 16 years old. She turned to have the fourth molar, «wolf tooth», canine teeth, the canine teeth of the lower jaw displaced forward and adjoined incisors